2017
DOI: 10.1080/10641963.2017.1356842
|View full text |Cite
|
Sign up to set email alerts
|

A case control association study of ACE gene polymorphism (I/D) with hypertension in Punjabi population from Faisalabad, Pakistan

Abstract: Angiotensin converting enzyme (ACE) is a key component of renin angiotensin aldosterone system. It converts angiotensin I to angiotensin II. Insertion/deletion (I/D) polymorphism of ACE gene is found associated with several complications. However, its association with hypertension and related metabolic diseases is still controversial. So, the aim of the present study was to check this association for Punjabi population from Faisalabad, Pakistan. For this purpose, blood samples (patients = 100, controls = 48) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
2
14
0
3
Order By: Relevance
“…Some of these peptides may inhibit the angiotensin-converting enzyme (ACE), a transmembrane zinc metallopeptidase that is related to hypertension (Seppo et al, 2003;Beermann and Hartung, 2013;Zoumpopoulou, 2016). Inhibiting ACE is an important strategy for controlling clinical hypertension (Hussain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these peptides may inhibit the angiotensin-converting enzyme (ACE), a transmembrane zinc metallopeptidase that is related to hypertension (Seppo et al, 2003;Beermann and Hartung, 2013;Zoumpopoulou, 2016). Inhibiting ACE is an important strategy for controlling clinical hypertension (Hussain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, this association is variable when diabetes co-occurs with CVDs. Our previous study has also showed the association of ACE I/D polymorphism with hypertension [13]. To further refine our results and to add more data, the current study was carried out with more sample number to mainly focus on the association of ACE I/D polymorphism with development of diabetes in cardiac patients.…”
Section: Introductionmentioning
confidence: 79%
“…This gene consists of 26 exons and encodes 2 transcript variants [9]. Insertion/Deletion (I/D) polymorphism (rs4340) consisting of 287 bp Alu repeats in intron 16 of ACE is extensively studied polymorphism, involved in controlling the plasma ACE activity [10] and found associated with various metabolic diseases [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Linie auf ACE, welchem durch die Umwandlung von Angiotensin I zu II eine Schlüsselrolle zukommt. In einer aktuellen Studie aus Indien wurde ein I/D-Polymorphismus (I/D: Insertion/Deletion) des ACE-Gens bei 61 % der untersuchten Hypertoniepatienten im Vergleich zu 41 % bei den gesunden Mitgliedern der Kontrollgruppe beobachtet [45]. Dabei zeigte sich eine signifikante Assoziation des DD-ACE-Genotyps mit einem höheren systolischen Blutdruck.…”
Section: Merkeunclassified